Two stages fault detection method based on error, applied in EBM facility - Ghazali A.B.; Hasan A.B. (American Institute of Physics Inc., 2023)
Data driven technique is a well-known method in fault detection and it is suitable for large industrial systems. In this article, this technique is applied in an electron beam (EB) facility to assist the technology available in that facility so that the number and cost of equipment/component failures can be reduced. An example is on EB scanning, if not properly monitored and in case of beam scanning unit fails, it will damage EB accelerator tube which is one of the main components in EBM facility. For these two stages fault detection, the current data for both x- & y- coils are monitored and compared with the normal outputs that obtained from such as an ANFIS model. If either or both errors are larger than their threshold limits and it happened for a certain period of time then the beam current source shall be terminated and the high voltage power supply across the tube shall be quickly reduce to 0 kV in order to avoid heat developed on the 25 ?m titanium foil window that due to electron beam penetration and will soon torn the window. Delays for three cases (x-, y- and both x&y coils) are pre-determined by the specialist and these will eliminate uncertainty of error signals.